Beyond Thalassocracies understanding processes of minoanisation and mycenaeanisation in the Aegean - Gorogianni, Evi; Pavúk, Peter 1974- (Oxbow Books, 2016)
"Beyond Thalassocracies aims to evaluate and rethink the manner in which archaeologists approach, understand, and analyse the various processes associated with culture change connected to interregional contact, using as a test case the world of the Aegean during the Late Bronze Age (c. 1600-1100 BC). The 14 chapters compare and contrast various aspects of the phenomena of Minoanisation and Mycenaeanisation, both of which share the basic underlying defining feature of material culture change in communities around the Aegean. This change was driven by trends manifesting themselves in the dominant palatial communities of each period of the Bronze Age. Over the past decade, our understanding of how these processes developed and functioned has changed considerably. Whereas current discussions on Minoanisation have already been informed by more recent theoretical trends, especially in material culture studies and post-colonial theory, the process of Mycenaeanisation is still very much conceptualised along traditional lines of explanation. Since these phenomena occurred in chronological sequence, it makes sense that any reappraisal of their nature and significance should target those regions of the Aegean basin that were affected by both processes, highlighting their similarities and differences. Thus, in the present volume we focus on the southern and eastern Aegean, in particular the Cyclades, Dodecanese, and the north-eastern Aegean islands"...From publisher's website
Includes bibliographical references and index
Keywords: Funde; Geschichte; Civilization, Aegean; Minoans; Civilization, Mycenaean; Bronze age -- Aegean Sea Region; Acculturation -- Aegean Sea Region -- History -- To 1500; Material culture -- Aegean Sea Region -- History -- To 1500; Regionalism -- Aegean Sea Region -- History -- To 1500; Social change -- Aegean Sea Region -- History -- To 1500; Social archaeology -- Aegean Sea Region; Akkulturation; Minoische Kultur; Mykenische Kultur; Aegean Sea Region -- Antiquities; Ägäis; Konferenzschrift -- 2013 -- Seattle, Wash.